Marjorie Barstow and the Alexander Technique - Cole, Amanda. author. aut Link
XXXVII, 327 p. 44 illus., 6 illus. in color.
Keywords: This book focuses on the teaching and philosophy of the pioneering performing arts teacher and educator Marjorie Barstow. She is one of the best and brightest exponents of the Alexander Technique (AT), an approach to awareness and movement widely deployed and valued in the performing arts and outside artistic circles. By comparing her approach to the educational philosophy of John Dewey, this book resurrects Marjorie Barstow’s name, and gives her pedagogy and legacy the attention it deserves.